Distribution of “Invisible” Noble Metals between Pyrite and Arsenopyrite Exemplified by Minerals Coexisting in Orogenic Au Deposits of North-Eastern Russia - Tauson V.L.; Lipko S.V.; Kravtsova R.G.; Smagunov N.V.; Belozerova O.Yu.; Voronova I. (My University, 2019)
The study focused on the forms of occurrence and distribution of hidden (“invisible”) noble metals (NMs = Au, Ag, Pt, Pd, Ru) in the coexisting pyrites and arsenopyrites of four samples of mineral associations from three Au deposits in the north-east of Russia. The unique nature of our approach was the combination of methods of local analysis and statistics of the compositions of individual single crystals of different sizes. This allowed us to take into account the contribution of the surface component to the total NM content and to distinguish the structurally bound form of the elements. The following estimates of the distribution coefficients of the structural (str) and surficial (sur) forms of elements were obtained: 𝐷𝑠𝑡𝑟𝑃𝑦/𝐴𝑠𝑝 = 2.7 (Au), 2.5 (Pd), 1.6 (Pt), 1.7 (Ru) and 𝐷𝑠𝑢𝑟𝑃𝑦/𝐴𝑠𝑝 = 1.6 (Au), 1.1 (Pd), 1.5 (Pt and Ru). The data on Ag in most cases indicated its fractionation into pyrite (𝐷𝑠𝑡𝑟𝑃𝑦/𝐴𝑠𝑝 = 17). Surface enrichment was considered as a universal factor in “invisible” NM distribution. A number of elements (i.e., Pt, Ru, Ag) tended to increase their content with a decrease in the crystallite size in pyrite and arsenopyrite. This may be due to both the phase size effect and the intracrystalline adsorption of these elements at the interblock boundaries of a dislocation nature. The excess of metal (or the presence of S vacancies) in pyrite increased Ag and Pt content in its structure and, to a lesser extent, the content of Ru, Pd and Au. Arsenopyrite exhibited a clear tendency to increase the content of Pt, Ru and Pd in samples with excess As over S. Sulphur deficiency was a favourable factor for the incorporation of Ag and platinoids into the structures of the mineral associations studied. Perhaps this was due to the lower sulphur fugacity. Pyrite with excess Fe was associated with higher contents of some NMs. The presence of other impurity elements was not an independent factor in NM concentration.
Keywords: noble metals; invisible species; distribution; pyrite; arsenopyrite; structural and surficial modes